EVALUATING STRATEGIC THINKING IN MANAGERS OF EXECUTIVE ORGANIZATIONS, GUILAN (Singaporean Journal of Business Economics and Management, 2013)
Problems and difficulties in organizations are going to be more complex, and solving them requires more effective solutions. Strategic planning is not necessarily an applicable program, and overtime undergoes changes, and in some cases, instead of solving organizational problem, just relief it, and as a result of losing their effect will lead to greater problems. It seems that requirement of developing and implementing strategic planning in organization is presence of strategic thinking among managers, who develop program. This paper tries to evaluate strategic thinking within managers of Guilanian executive organizations through "Jeanne Liedtka" model. This model includes five main indicators, which are "System Perspective", "Inter Focus", "Hypothesis Drive", "Intelligent Opportunism", "Thinking in Time"; they have divided to 29 sub-factors by contributing available resources and expert's ideas; and through using survey-descriptive method the importance of factor and current status of each mentioned indicators have been evaluated by T-questionnaire of managers in Guilanian executive organizations. Analyzing results by Friedman and paired test indicate that despite significant operations, such as developing strategic documents in Guilan executive organizations, there is a significant differences between the importance of their main factors and current status in the organization, which paying attention them is inevitable.